Global, regional, and national burden of high body-mass index-related cancers and associated preventable life expectancy loss from 1990 to 2021 - Huang, Ling; Wang, Dongdong; Li, Pinyi; Liang, Xinger (Frontiers in Nutrition, 2025)
BackgroundA high Body Mass Index (BMI) is a key modifiable risk factor for cancer incidence. Therefore, it is essential to monitor the evolving trends and impact of cancer linked to high BMI and to formulate suitable strategies to address this issue. This study aims to analyze, from 1990 to 2021, the burden and temporal trends of cancer attributable to BMI as well as their impact on life expectancy, with major patterns highlighted by sex, socio-demographic index (SDI), and geographical region.MethodsUtilizing data from the Global Burden of Disease Study 2021, which incorporates 328,938 data sources, we conducted a comprehensive analysis of cancer attributable to high BMI, specifically investigating mortality rates and disability-adjusted life years (DALYs) from 1990 to 2021. Age-standardized rates were used to facilitate cross-regional comparisons, accounting for differences in population size and demographics. The Socio-demographic Index (SDI) was employed to categorize regions and evaluate correlations between cancer burden and economic development. In addition, we used the abridged period life table to estimate the impact of high BMI-related cancer on life expectancy.ResultsThe age-standardized death and DALY rates of cancer linked to high BMI increased (average annual percent change, 0.4 (95% UI: 0.4–0.5) for mortality and 0.5 (95% UI: 0.4–0.6) for DALY) from 1990 to 2021. The age-standardized death and DALY rates of cancer associated with high BMI were higher in females than in males globally. The alarming proportional increase in deaths from the main cancer associated with high BMI was observed among younger age groups (<45 years) from 1990 to 2021. In 2021, the most significant increases in life expectancy at birth were observed in regions with a high socio-demographic index, with gains of 0.12 (95% CI: −0.45–0.69) years for males and 0.19 (95% CI: −0.35–0.73) years for females, respectively. It is predicted that the age-standardized death rate of cancer attributable to high BMI will increase from 3.31 (3.29–3.33) in 2021 to 3.32 (1.27–5.37) by 2046 in males, and from 4.36 (4.38–4.39) to 4.90 (1.96–7.86) in females.ConclusionThe age-standardized mortality and DALY rates of cancer linked to high BMI have increased substantially, with significant differences across sex, geographic region, and SDI. Interventions aimed at reducing exposure are crucial not only to mitigate the cancer burden attributable to high BMI effectively, but also to yield modest gains in life expectancy.